Structure of the Tortricid-Parasitoid community in a recently introduced blueberry crop. - Rocca, Margarita (2015)
The introduction of exotic commercial plants represents a change in the food resources for the communities of herbivores. The blueberry is native to the northern hemisphere and was recently introduced in Argentina, so we expect to find polyphagous tortricids and a low complexity in the tortricid–parasitoid community. Tortricids are exophytic leaf-rollers and flower and fruit feeders, they can feed on different plant structures, and they may be present in every blueberry phenological stage. The aims of this study were (a) to estimate the relative abundance of tortricids in different plant structures and phenological stages of blueberry, (b) to evaluate the relative importance of the different parasitoid guilds, and (c) to describe the tortricid–parasitoid community in blueberry fields of Argentina. The abundance of tortricids in blueberries was low and mainly localized to flowers and fruits. Five parasitoid guilds were identified: early larval endoparasitoids (Apanteles sp. and Dolichogenidea m1 and m2), larval–prepupal endoparasitoids (Austroearinus sp.), larval–pupal endoparasitoids (Ichneumonidae), larval ectoparasitoids (Eulophidae), and pupal endoparasitoids (Brachymeria sp. and Conura sp.). Most parasitoids were koinobiont larval endoparasitoids. The tortricid–parasitoid food web was very simple in comparison to those of other systems, with high values of vulnerability and connectance. The results of this study suggest that the abundance of tortricids in blueberry crop in Argentina is low. From the point of view of production, the risk of economic losses and the likelihood of direct damage to the fruit would be very low.